A polyoxometalate-based self-cleaning smart material with oxygenic activity for water remediation with membrane technology. (June 2021) - Galiano, Francesco; Mancuso, Raffaella; Carraro, Mauro; Bundschuh, Jochen; Hoinkis, Jan; Bonchio, Marcella; De Luca, Giorgio; Gabriele, Bartolo; Figoli, Alberto
Highlights: A new answer for fouling remediation in membranes for wastewater treatment. Design and development of a novel smart material with oxygenic activity. H2 O2 dismutation catalyst chemically incorporated into the material polymeric network. Functionalization of commercial membranes by smart material coating. Production of innovative self-cleaning membranes for water treatment applications. Abstract: An unprecedented solution for alleviating non-restorable fouling in water treatment membrane processes is herein proposed and described. A novel smart material with oxygenic activity was developed starting from a polymerizable bicontinuous microemulsion (PBM) containing a surfactant encapsulated polyoxometalate (SEP) as catalyst. This material (PBM-SEP) was used for the surface functionalization of commercial ultrafiltration (UF) membranes by allowing the polymerization of the SEP-containing PBM to take place after casting on membrane surface. This has allowed obtaining a composite membrane with self-cleaning properties toward non-restorable fouling, thanks to the oxygenic activity of the embedded catalyst, resulting from H2 O2 dismutation. The newly developed smart material may find practical application to implement membrane technology for an efficient wastewater treatment. Graphical abstract: Image, graphical abstract